The baby-sitters clubClaudia and the bad joke Claudia and the bad joke - Nopra, Arley (New York, NY Graphix, an imprint of Scholastic, 2024)
While baby-sitting for practical joker Betsy Sobak, Claudia breaks her leg as a result of one of Betsy's pranks and wants to quit the club, prompting Kristy and the other baby-sitters to teach Betsy a lesson.
"Based on the novel by Ann M. Martin"--Cover.
Ages 8-12